NEW MAMMOTH FIND IN CHUKOTKA - Lozhkin A.V.; Zadal'skiy S.V.; Pavlov G.F.; Ryabchun V.K.; Gorbachev A.L.; Shubert E.Y. (My University, 1988)
In November 1986, in the course of mining operations in the Enmynveyem R. valley in the Bilibin district of the Magadan region, the remains of a new mammoth were discovered. For radiocarbon dating of the time of the animal's death, small bits of hide, muscle and connective tissue were taken, and a date of 32,850 ± 900 years was obtained on them. This corresponds to the Konoshel' skiy cooling of Siberia, which occurred in the Northeast Territory of the USSR in the interval of 33 to 30 thous. yrs. ago. The deposits directly enclosing the mammoth leg were sampled for palynological analysis. We believe, on the basis of the palynological data, that at the time the Enmynveyem mammoth died about 33 thous. yrs. ago, climatic conditions harsher than today's existed in the central regions of Chukotka.